The Learning Potential Assessment-2 in Yaqui Native American children - Frannia Aglaé Ponce-Zaragoza; María Teresa Fernández-Nistal (LED Edizioni Universitarie, 2019)
The aim of this study was to determine if the Learning Potential Assessment-2 (EPA-2) can be an adequate instrument for assessing the learning potential in Yaqui Native American children living in Sonora, Mexico. The participants were 89 students from three second grade primary schools divided into an experimental and control groups matched on IQ and age. Both groups were assessed by tests of intelligence. The experimental group was trained with a dynamic testing methodology. The results show a significant difference between the means of the posttest gain scores in the experimental and control groups with a high effect size. There was a temporary stability of the gained scores, because no significant difference between the posttest and the retest were found in a period of three months in the experimental group. In conclusion, the EPA-2 may be useful as dynamic testing for learning potential for this ethnic group and educational level.